The bureaucratic class: a dissent on pedersen - Ghosh B.N.
In the 1980s, a growing section of the Indian intellectuals opinion considered the Indian state and its permanent personnel, mainly bureaucracy, responsible for the slow growth of the Indian economy. According to this predominant view, Indian bureaucracy has had an independent power to frame and guide the policies of the state. Because of its power to control and determine the regulatory function of the state and large public enterprises, the bureaucracy in the course of time became the supreme powerful class in India both economically and politically. Pedersen has advanced three main stands of arguments to challenge the dominant class hypothesis. First, he has attempled to disprove the pheno men on of growth/e
Keywords: Bureaucrates -- India; Civil Service -- India